Mind Mapping in Learning Models: A Tool to Enhance EFL Students in Descriptive Text Writing (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2025)
This study aimed to improve Grade X students’ descriptive writing skills through the application of mind mapping. This research was conducted at Diponegoro Depok Vocational School in Sleman, Yogyakarta. The participants of the study were 20 students who were identified as having difficulties in organizing and expressing ideas in written form. The research was carried out over 11 meetings, including a pre-test, two action cycles (each comprising three meetings), and a post-test. Data were collected using writing tests, observation sheets, interviews, field notes, and documentation, and analyzed through both quantitative and qualitative approaches. The quantitative analysis assessed improvements in students’ scores based on a rubric adapted from Brown (2010), while the qualitative analysis used thematic content analysis to explore student engagement and creativity. The results showed significant improvement in both individual and classical mastery levels, with students demonstrating enhanced organization, vocabulary, and idea development. The findings suggest that mind mapping is an effective technique for enhancing descriptive writing and fostering 21st-century skills such as collaboration, creativity, and critical thinking. This study highlights the value of CAR as a reflective, data-driven approach to improving teaching practices and student outcomes.